CARBOPLATIN INDUCED ISCHEMIC OPTIC NEUROPATHY - Dr. Nitin Mehrotra, Dr. Rachit Rastogi, Dr. G.S. Titiyal, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Cisplatin and carboplatin are the two platinum based alkylating agents usedwidely as anti-cancer therapy. Carboplatin is more chemically stable and better tolerated withcomparatively favourable profile. Reports of Carboplatin precipitating optic neuropathy israrely reported.